Cemiplimab- and nivolumab-induced myasthenia gravis: two clinical cases. Issue 6 (December 2021) - Canino, Fabio; Pugliese, Giuseppe; Baldessari, Cinzia; Greco, Stefano; Depenni, Roberta; Dominici, Massimo
Immune-related myasthenia gravis is a rare, disabling, and potentially fatal adverse event of immune checkpoint inhibitor treatment. It is important to identify and manage it promptly. We present two cases of immune-related de novo myasthenia gravis observed at the Modena Cancer Center in two elderly patients treated with two anti-PD-1 monoclonal antibodies: cemiplimab and nivolumab.